In vivo and in vitro evolution of the effects of cypermethrin on turbot (Scophthalmus maximus, Linnaeus, 1758) spermatozoa - Beken, Atife Tuba; Saka, Sahin; Aydin, Ilhan; Firat, Kursat; Suzer, Cuneyt; Benzer, Fulya; Antepli, Onurkan (Elsevier Science Inc, 2022)
Synthetic pyrethroid pesticide is commonly used in agricultural activities in the Black Sea region during reproduction period of turbot. In this sense, in vivo and in vitro studies have shown that cypermethrin (CYP) could be one of the environmental factors affecting decreasing turbot stocks. In this study, effects of in vivo and in vitro administration of CYP, a synthetic pyrethroid, on sperm kinematics motility (MOT), progressive motility (PM), curvilinear velocity (VCL), straight line velocity (VSL), average path velocity (VAP), linearity (LIN), straight line velocity (STR), amplitude of lateral head (ALH), beat cross frequency (BCF), oxidative stress biomarkers malondialdehyde (MDA), reduced glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and lipid peroxidation (LPO) and also histopathological alterations in gonads were investigated in spermatazoa of turbot (Schopthalmus maximus). Broodstock was supplied from culture origin and used in spawning season, additionally, two (0, 0.187 and 0.218 ppb) and three (0, 1.025, 2.05 and 4.1 ppb) different CYP concentrations were performed for in vivo and in vitro studies, respectively. In vivo and in vitro studies, significant reductions were found in sperm MOT, PM, VCL, VSL, VAP, LIN, and ALH properties depend on the increase in CYP concentrations (p < 0.05). Besides, activities of GSH, GPx, SOD, and CAT increased. In terms of histological alterations, no difference was observed among groups (0, 0.187 and 0.218 ppb) in the maturity stage of the germ cells. According to obtained results, sperm kinematics was affected significantly with increased the dose levels of CYP (p < 0.05).
Keywords: Scopthalmus maximus; Turbot; Cypermethrin; Sperm kinematics; Oxidative stress; Antioxidant activity; Histopathological changes